Representações sociais sobre sexualidade e educação sexual: um estudo com professores da rede pública de ensino de Cuiabá-MT - 2005-2009 - Oliveira, Rita Aparecida Pereira de (2009)
In this research we try to verify which is the knowledge on Sexuality that sustains the social representations of Sexual Education in the everyday life of 56 teachers from public schools in Cuiabá - Mato Grosso, interviewed in year 2006. The interdisciplinary dimension of the Theory of Social Representations (MOSCOVICI, 1978; JODELET, 2001) has enabled us to make an articulation with references of Foucault (2007). Considering the complex nature of the objects, we have sorted out the discursive materials, initially processed by the Alceste software, and have subsequently used the Content Analysis for Sexuality data only. The results outlined by the three classes of words reveal that the production of knowledge on sexuality happens in view of the sexual doubts of students and curiosities on the sexuality of teachers. These, when talking about the other talk about themselves and manifest aspects of their social practices and interactions not always dialogical because they remain between question and answer. Teachers self-assess themselves as unqualified, and anchor their restlessness on the word embarrassed when expressing their opinion on the compartmented education. Feelings, values and opinions have surrounded the symbolic role of the representation of sexuality starting from incidents that mediate the relations. There are five classes that guide the lexical analysis of Sexual Education. Knowledge and Precepts deal with sporadic actions that share space with Sexual Health actions. The transversality objectified in Science and Biology seems to associate sexuality with anatomical and physiological aspects corroborated by other results. These subjects, counterbalanced by the Portuguese Language discipline, show affinity to discuss this theme. Teachers analyze that the teaching of sexuality requires systematization, but no projects exist. Social representations of Sexual Education are anchored on values such as the family, which sets limits; the media, represented by the negative nature, which stirs up more than teaches; the naked truth confronts the world objectified in diseases and precocity of adolescents. The school, less frequently, emerges with the psychopedagogical ideal of teaching to value body and life. Sexuality topics proliferate and are spread within the school context, in view of dialogue-encouraging episodes that happen inside it. However, just as the theme is not much shared with students, the co-workers are also not always called to share the anxieties they experience, save when these extrapolate cases of student pregnancy. In fortuitous events that involve parents, these seem to break the social rules of the secret on sex, which is perpetuated in the school and the family. The speech returns on the educators involved, who sometimes, feeling guilty and surprised, receive the burden of the responsibility, as if it were a transgression to discuss the subject. Therefore, in an attempt to organize elements that form the SR of Sexual Education, we would say that they are seized from three scopes: sexuality and knowledge, where we observe the form of interaction starting from communication and practices; sexuality and education, which catch a glimpse of the professional identity aspects, and sexuality and socio-cultural environment, where deponents support each other to mold the building of the Sexual Education object circled by mental, socio-cognitive and affective aspects